2020
DOI: 10.1111/1541-4337.12617
|View full text |Cite
|
Sign up to set email alerts
|

Control of pathogenic and spoilage bacteria in meat and meat products by high pressure: Challenges and future perspectives

Abstract: High-pressure processing is among the most widely used nonthermal intervention to reduce pathogenic and spoilage bacteria in meat and meat products. However, resistance of pathogenic bacteria strains in meats at the current maximum commercial equipment of 600 MPa questions the ability of inactivation by its application in meats. Pathogens including Escherichia coli, Listeria, and Salmonelle, and spoilage microbiota including lactic acid bacteria dominate in raw meat, ready-to-eat, and packaged meat products. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 195 publications
0
16
0
Order By: Relevance
“…Lastly, biological applications include bacteriophages and wrapping film with postbiotics containing lactic acid bacteria. However, all applications must take into account meat quality and the physiology of the end product (Bolumar et al, 2020;Li et al, 2020;Shafipour Yordshahi et al, 2020;Aydin Demirarslan et al, 2021).…”
Section: Amr In the Slaughtering Processmentioning
confidence: 99%
“…Lastly, biological applications include bacteriophages and wrapping film with postbiotics containing lactic acid bacteria. However, all applications must take into account meat quality and the physiology of the end product (Bolumar et al, 2020;Li et al, 2020;Shafipour Yordshahi et al, 2020;Aydin Demirarslan et al, 2021).…”
Section: Amr In the Slaughtering Processmentioning
confidence: 99%
“…High-pressure processing is a commercialized technology that inactivates or kills microorganisms to extend the shelf life and maintain the good sensory quality of seafood; however, some microorganisms (e.g., Staphylococcus aureus , E. coli , Salmonella enterica ) can survive high-pressure treatment ( Zhao et al, 2019 ; Li et al, 2020 ). In this study, a high-pressure-tolerant strain of N11 was evolved from the wide-type strain of C4 after eight rounds of high-pressure treatment ( Figure 2A ), and the survival rate of the N11 showed that it could tolerate 200 MPa treatment ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of high-pressure-induced inactivation of microorganisms involves cell membrane lipid damage, intracellular pH shifts by solute transport, metal ion release, enzyme deactivation, and decreased DNA synthesis ( Patrignani and Lanciotti, 2016 ; Nikparvar et al, 2021 ). Unfortunately, a small number of both Gram-positive and Gram-negative bacteria can survive after 400–600 MPa HPP treatment for 8 min ( Li et al, 2020 ), and their survival might lead to contamination with living microbes that can pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that lactic acid bacteria are more resistant to high pressure than other microorganisms. This opens up wide opportunities for the development of fermented products with an extended shelf life, as the spoilage pathogens and microorganisms can be effectively eliminated while the microorganisms derived from the starter cultures remain viable [ 6 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%